Effects of recreational football on body composition, cardiometabolic health, and functional performance in children and adolescents: a systematic review and meta-analysis - Lei, Yanzhao; Ding, Yanmei; Wang, Bo; Deng, Hengzhi; Yin, Mingyue; Xu, Kai; Liu, Hengxian; Tao, Meiling; Li, Yanfeng; Zhang, Yilin; Liu, Yuhang; Meng, Fanhao; et al. (Frontiers in Physiology, 2026)
PurposeThe systematic review and meta-analysis aimed to evaluate the effects of recreational football on body composition, cardiometabolic health, and functional performance in children and adolescents. Additionally, it explored potential moderators through subgroup analyses.MethodsA systematic search was conducted in six databases in May 2025. A random-effects model was employed for the meta-analysis, and effect sizes were reported as standardized mean differences (SMD, Hedges’ g). Subgroup and sensitivity analyses were conducted to examine sources of heterogeneity.ResultsA total of 20 studies (N = 2,906; age range: 8–17 years) were included. Of the participants, 1,524 (52.44%) were male, 1,174 (40.40%) were female, and 208 (7.16%) did not clearly report their gender. Recreational football significantly reduced BMI (SMD = −0.13 [−0.24, −0.02]), body fat percentage (SMD = −0.37 [−0.63, −0.11]), and waist circumference (SMD = −1.38 [−2.65, −0.11]), with a slight increase in lean mass (SMD = 0.13 [0.02, 0.24]). It also reduced mean arterial pressure (SMD = −1.06 [−2.03, −0.10]), systolic blood pressure (SMD = −0.71 [−1.19, −0.23]), and triglycerides (SMD = −0.95 [−1.74, −0.15]), while having no effect on diastolic blood pressure, resting heart rate, VO2peak, blood glucose, or cholesterol. Additionally, it improved interval endurance (SMD = 0.15 [0.04, 0.25]), sprint speed (SMD = −0.72 [−1.22, −0.22]), standing long jump (SMD = 0.53 [0.10, 0.97]), and balance (SMD = 0.84 [0.21, 1.46]), but had no effect on vertical jump. Subgroup analyses showed greater reductions in BMI (g = −0.54) and body weight (g = −0.89) in overweight/obese individuals, and significant weight improvement in adolescents >12 years (g = −1.35). Longer interventions (≥12 weeks) and higher frequencies (>2 sessions/week) were associated with greater body fat reduction (g = −0.82 and g = −0.74), with reductions in resting heart rate observed mainly in interventions ≥12 weeks (g = −0.72). According to the GRADE assessment, the overall quality of evidence was rated as low to very low.ConclusionRecreational football is efficacious in improving body composition, select cardiometabolic risk factors, and physical performance in children and adolescents, especially individuals classified as overweight or obese. Even with limitations in sample size, intervention diversity, and methodological quality, resulting in an overall low to low quality assessment of the evidence, the comprehensive evidence still provides preliminary quantitative support for incorporating recreational football into youth health promotion; future efforts will require larger samples, standardized protocols, and rigorous design to enhance the strength of the evidence. Based on existing evidence, a reference protocol may consist of a 12-week program with 2–3 weekly sessions (45–60 min each), including a FIFA 11+ warm-up, 3–4 bouts of 4–6 min at up to 80% HRmax with 2-min recovery intervals, and a cool-down.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD420251106734, identifier CRD420251106734.